(untitled) (Vietnam Journal of Community Medicine, 2020)
Objective: To assess compliance and some factors related to medicine use of patients with type 2 diabetes mellitus at Nam Can District General Hospital, Ca Mau Province. Objects and methods: Cross-sectional study on 528 outpatients with type 2 diabetes treatment at Nam Can District General Hospital, Ca Mau province from July 2019 to April 2020. Results: Adherence rate to drug use in type 2 diabetic patients: 40 patients (7.6%) had high compliance level with using medicine, 274 patients had moderate compliance level (51.9%) and 214 patients had poor compliance level (40.5%). There was one factor related to drug adherence: occupation (OR = 0.053; 95% CI = 0.372-1.007. Conclusion: mainly patients with moderate and low compliance levels. Occupation was related to compliance of using medicine.